EVALUASI PENERAPAN PRINSIP KESEHATAN DAN KESELAMATAN KERJA (K3) PADA PELAKSANAAN KEGIATAN PRAKTIKUM MIKROTEKNIK DI LABORATORIUM BIOLOGI FAKULTAS SAINS DAN TEKNOLOGI UIN SUNAN KALIJAGA - Ethik Susiawati Purnomo; Dony Eko Saputro (Integrated Lab Journal, 2018)
The aim of this research was to determine the implementation of the principles of health and safety in Microtechnic Laboratory Practice. This research was a qualitative study with descriptive quantitative data analysis. The data were obtained using several instruments: questionnaires, field observation and interview sheets to the lecturers and laboratory assistants. The application of the principles of health and safety, especially in using personal protective equipments is not maximized implemented. Found some students did not wear the personal protective equipments while Microtechnic laboratory practice lasted. The students awareness of the importance of health and safety in the work place needs special attention from the laboratory practices manager for safety and comfort during laboratory activities.